Huge gangrenous gallbladder presenting as gastro-esophageal reflux disease successfully treated by laparoscopic cholecystectomy: Case report and literature review. (2020) - Elkbuli, Adel; Meneses, Evander; Kinslow, Kyle; McKenney, Mark; Boneva, Dessy
Highlights: "Giant" gallbladder development in the context of acute on chronic cholecystitis is extremely rare and may present with atypical symptoms secondary to mass effect. Current grading systems for acute cholecystitis severity do not include assessment based on size making them insufficient in predicting "giant" gallbladder surgical prognosis. Laparoscopic cholecystectomy was performed successfully despite the large gallbladder size without intraoperative/postoperative complications. Abstract: Introduction: Gallbladder disease is a common surgical pathology. Gallstones can remain asymptomatic or develop into an acute cholecystitis and need for surgical intervention. Significant enlargement of the gallbladder well beyond the normal volume is rare. Such "giant" gallbladders can affect feasibility of subsequent management options. Presentation of case: An 80-year-old female presented to the emergency department with a two-day history of acute on chronic gastric reflux with nausea and vomiting. On examination, she had right upper quadrant abdominal pain. CT imaging identified an enormous gallbladder creating mass effect and compression on the distal stomach. She underwent successful laparoscopic cholecystectomy and was discharged from the hospital the next day, doing well. On two-week follow up, her reflux symptoms had completely resolved and she had no complaints. Discussion: Giant gallbladders are a rare entity. Our patient's case is unique in both its occurrence as well as presentation with predominant reflux symptoms secondary to mass effect by the enlarged gallbladder. Current cholecystitis grading systems do not utilize size as a means of predicting severity and risk of operative complications or difficulty of procedure. Laparoscopic cholecystectomy was a successful approach in managing this extreme pathology. Conclusion: Updated classifications systems that include size and mass effect as a predictive measure are needed to better assess surgical outcomes, especially in "giant" gallbladder disease. Despite the large size and potential mass effect on surrounding structures, laparoscopic cholecystectomy can still be attempted if no other contraindications exist.